OP0043 Prolonged Assumption of HCQ is Associated with Longer Survival in Sle. (10th June 2014) - Fredi, M.; Cavazzana, I.; Taraborelli, M.; El Masri, Y.; Martinazzi, N.; Tincani, A.; Franceschini, F.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disorder that can be severe and life threatening. Death in patients with SLE may be due to many factors, including persistent lupus activity, complications of treatment, or to long-term sequelae. Objectives: The aim of our study was to evaluate an advantage on surviving in SLE patients related to treatment. Methods: We retrospectively evaluated 120 SLE patients, attending our outpatients Clinic, from 1983 to 2013, revised according to SLICC/ACR criteria [1]. Patients were divided into 2 groups: dead patients (n=38) and control group of patients alive (n=82). Clinical, laboratoristic and treatment data were obtained from clinical charts. SLE activity was calculated with Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) at the onset and while damage was evaluated with System Lupus International Collaborating Clinics/ACR Damage Index for Systemic Lupus Erythematosus (SLICC) at the last visit. Two-tailed Student's t-test for continuous variables and Fisher's exact test or Yates's Chi squared test for categorical variables were used. Results: clinical manifestations and autoantibodies profile did not show statistical differences among the groups; also the mean age at the onset (36.5 vs 35.6 years) and duration of the disease (14 vs 16 years) were similar. Disease activity at the onset in the deceased group, obtained with SLEDAI-2K, was significantly lower than controls (11.3 vs 8.7; p=0.015), while SLICC/ACR damage index calculated at the last visit was not statistically significant (1.9 vs 2.5; p=n.s). The most frequent causes of death were cancer (12 patients) and circulatory disease (10 patients), while SLE was the assigned cause of death in 2 cases. Assumption of hydroxychloroquine was less frequent (55% vs 87%, p≤0.0001, OR 0.17; CI95% 0.05-0.47) and duration of assumption was shorter among patients dead than alive controls (31 vs 72 months, p=0.0002). The number of the patients that assumed steroids among the two groups was not different (94.7 vs 93.9%) but deceased patients received a mean daily dosage higher than alive (12 mg/day of prednisone equivalent vs 8.4 mg/day; p=0.01), and higher number of deceased patients received a daily dosage of prednisone equivalent more than 12.5mg (31% vs 13%; p=0.025, OR 2.97; CI95% 1.06-8.38). Comparison between the deceased patients that received more than 12.5mg of steroid versus lower dosage revealed that the subgroup that received a higher dosage was more frequently treated with at least one immunosuppressant drug than the other subgroup (91.6% vs 45.8%, p=0.01, OR 13; CI95%1.30-30); moreover SLEDAI-2K at the onset was higher among deceased patients treated with higher dosage of steroid than the other deceased patients (11.1 vs 7.31, p=0.01); while SLICC was higher but did not reach statistical difference (3.16 vs 2.19. p=0.06). Conclusions: Our preliminary result seems to confirm that the use of elevated dosage of steroids seems to be associated with higher disease activity, higher cumulative damage and a worse outcome; conversely prolonged assumption of hydroxychloroquine is associated with longer survival in SLE patients. References: Petri M, et al. Arthritis Rheum. 2012;64: 2677-86. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2658